2019
DOI: 10.4103/jispcd.jispcd_316_18
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of bidirectional relationship between periodontitis and hyperlipidemia

Abstract: Periodontal disease and hyperlipidemia are both multifactorial disease with a high prevalence Worldwide. Cross-sectional and longitudinal prospective clinical studies show some evidence for a bidirectional relationship. Periodontitis and hyperlipidemia share some common risk factors and there exist a mechanistic link between both. Studies have found a positive response to periodontal therapy among hyperlipidemic patients, and statin use by hyperlipidemic patients has shown to influence the periodontal health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 78 publications
(85 reference statements)
0
17
0
2
Order By: Relevance
“…As far as other metabolic syndrome components are concerned, there is evidence in the literature that the anomaly of lipid metabolism in the blood may affect periodontal disease progress [ 53 , 54 ]. Animal studies have shown that dyslipidemia predisposes the host to oral infection by impairing proper immune response to bacteria challenge [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…As far as other metabolic syndrome components are concerned, there is evidence in the literature that the anomaly of lipid metabolism in the blood may affect periodontal disease progress [ 53 , 54 ]. Animal studies have shown that dyslipidemia predisposes the host to oral infection by impairing proper immune response to bacteria challenge [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…A. actinomycetemcomitans is considered an essential microbial factor in aggressive periodontitis, usually with early-onset and combined with various defects in the immune response [33,38]. It has been suggested that periodontal disease and the presence of periopathogens may influence lipid metabolism, inducing changes in the concentration of cytokines [40]. Recently Lee et al [41] proved that the prevalence of gingivitis in adolescents is positively correlated with low HDL-C level.…”
Section: Discussionmentioning
confidence: 99%
“…Low blood high-density-lipoprotein (HDL) levels were reported to be a risk factor for cardiovascular disease in many previous epidemiological studies [17]. In addition, Choi et al [18], Nepomuceno et al [19], and Abraham et al [20] reported that triglyceride level, HDL-cholesterol(HDL-C), and low HDL-C, respectively, are significantly associated with periodontitis.…”
Section: Discussionmentioning
confidence: 99%